Supreme Court's Ultra Vires Rulings Represent a Paradigm Shift in The Judicial Review Conducted by Constitutional Judges - Nabila, Larasati; Hidayat, Rayhan Naufaldi; Juaningsih, Imas Novita (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2022)
This study focuses on discussing the legal ratio of ultra vires rulings by constitutional judges as a manifestation of judicial activism. The ultra vires ruling has created a dialectic between preventing rechtvacum to uphold constitutional justice and the threat of judicial autocracy because the Constitutional Court exceeds its authority as a negative law. The purpose of this study is to comprehensively describe the dialectics of affirming ultra vires decisions by the Constitutional Court in accordance with human rights based on constitutional justice, as well as to analyze the application of the ultra vires doctrine to the actions of the Directors in hiring workers/labourers with work agreements for a certain time. The research method used is normative legal research with a legal approach and a contextual approach. The results of this study indicate that ultra vires decisions by constitutional judges are an unavoidable legal necessity. This is because normatively, sociologically, and in principle they are not contradictory. Therefore, ultra vires needs to be done with methods and sources to find the right law/constitutional to prevent rechtvacuum and overlapping judges in dealing with problems that are constantly changing without destroying checks and balances and creating a mini-parliament